A horvát-magyar-szerb hármashatár néhány társadalomföldrajzi aspektusa - Bali, Lóránt; Szalai, Gábor (Közép-Európai Közlemények, 2011)
The Croatian–Hungarian–Serbian tripartite border is one of the areas in the Carpathian Basin undergoing the greatest space structural changes. In the 90 years following the break-up of the Austro–Hungarian Monarchy the region had to face military agression and ad-hoc border changes. The most stable common denominator of those supporting and opposing the European Union is that they both consider the etherealization of borders the most important and the most determining achievement of the European integrational process. As a result of the multiethnic nature of the region, primarily we would like to examine the processes up to now from a national point of view concentrating on the future. Besides we are going to introduce the permeability of the border and the space structure of the area as well. In a cross border area the intensity of social-economic interactions is strongly influenced by the quality of the traffic network the density and permeability of border crossing points. Developments could be based on the cooperation of smaller regional centres, primarily built on microregional economic aspects (retail trade, agriculture, building trade, handicraft).